Stop motion : Craft skills for model animation - Shaw, Susannah (Amsterdam ; London : Focal, 2008)
"Provides a step by step guide to creating successful motion films. Starting with some basic exercises, readers will learn about developing a story, making models, creating sets and props, the mechanics of movement, filming, post production and how to set about finding that elusive first job in a modern studio."--Jacket
Introduction -- playing God -- Getting equipped -- Getting animated -- Keep it simple -- developing your story -- Coat hangers for armatures -- making your own model -- Model makers -- the professionals.
Previous ed.: London: Elsevier, 2004
BIBINDX
Keywords: Animation (Cinematography); Models and modelmaking